Spontaneous CD4+ and CD8+ T‐cell responses directed against cancer testis antigens are present in the peripheral blood of testicular cancer patients. Issue 7 (26th June 2017) - Pearce, Hayden; Hutton, Paul; Chaudhri, Shalini; Porfiri, Emilio; Patel, Prashant; Viney, Richard; Moss, Paul
Abstract : Melanoma‐associated antigen (MAGE) genes are frequently over‐expressed in cancer. Pearce and colleagues show that T‐cell responses against multiple MAGE‐A family antigens develop in many patients with testicular cancer, yet these responses progressively decline following treatment. It is possible that strong tumor‐specific immunity plays an important role in mediating the excellent clinical outcome of patients with this disease. Abstract : Cancer/testis antigen (CTAg) expression is restricted to spermatogenic cells in an immune‐privileged site within the testis. However, these proteins are expressed aberrantly by malignant cells and T‐cell responses against CTAgs develop in many cancer patients. We investigated the prevalence, magnitude and phenotype of CTAg‐specific T cells in the blood of patients with testicular germ cell tumors (TGCTs). CD8 + and CD4 + T‐cell responses against MAGE‐A family antigens were present in 44% (20/45) of patients' samples assayed by ex vivo IFN‐γ ELISPOT. The presence of MAGE‐specific CD8 + T cells was further determined following short‐term in vitro expansion through the use of pMHC‐I multimers containing known immunogenic peptides. Longitudinal analysis revealed that the frequency of MAGE‐specific T cells decreased by 89% following orchidectomy suggesting that persistence of tumor antigen is required to sustain CTAg‐specific T‐cell immunity. Notably, this decrease correlated with a decline in the global effector/memory T‐cell pool following treatment. Spontaneous T‐cell immunity against CTAg proteins therefore develops in many patients with testicular cancer and may play an important role in the excellent clinical outcome of patients with this tumor subtype.